Faktor-faktor Ergonomik yang Mempengaruhi Prestasi Kerja Kakitangan Kumpulan Sokongan di Jabatan Perangkaan Malaysia Negeri Kelantan - Azuraini, Arif (Universiti Malaysia Sarawak (UNIMAS), 2005)
The inappropriate and neglect of ergonomics principles in the job design, environment, and equipment design will brings negative effects to productivity and performance. The aim of this study is to look at the relationship between ergonomics factors such as job rotation, job enrichment, job enlargement, temperature, lighting, computers (keyboard, monitor, mouse) and furniture (desk, chair) with job performance among supporting staffs at Jahatan Perangkaan Malaysia Negeri Kelantan. 36 respondents were selected as a sample for this study and a survey questionnaire was used. för collecting data. From the Pearson Correlation Analysis, the findings revealed that there was a significant relationship between ergonomics factors such as computer (r=0.440, p=0.007) and furniture (r=0.614 p=0.000) with the job performance. The Linear Regression Analysis disclosed that the furniture was the dominant . factor that contributed to the workers performance (37.7%). Overall, results illustrate that the organization should emphasize on ergonomics factors in the office environment to enhance the job performance of the workers with the aim of preventing any occupational accidents or incidents